The impact of an information linkage system on a firm's organization structure, transfer price, and profit / Jumpei Hamamura. - Hamamura, Jumpei (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
This study investigates the impact of costless information linkage systems on the organization structure, transfer price, and profit of companies. These firms typically consist of a headquarters (HQ) and downstream divisions (DD). Recent research on management accounting emphasizes the importance of a firm choosing the optimal level of internal transfer price and organization structure to maximize its total profit. The study constructs an analytical model to analyze the optimal decisions a firm that faces price competition in a product market needs to make. Our mathematical analysis demonstrates that a firm’s profit declines when it adopts an information linkage system that mitigates the information asymmetry between the HQ and DD in a competitive price environment. This is a novel result, since prior management accounting research indicates that information linkages between intra-organization divisions improve the firm’s total profit. The result of this study is attributed to the loss of incentive for tacit collusion between competitors. The firm has no incentive to decide on the decentralization of decision rights by adopting an information linkage system. Therefore, this research has a significant implication for management accounting practice. Firms should exercise cautionwhen adopting an information linkage system, as – under specific economic conditions – it may not improve their profits.